Communication Strategy as a component of Silvio Berlusconi's political marketing - Marucciová, Nicoll; Olšanová, Květa; Jaroš, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This master thesis is investigating the successful components of a political communication strategy with the application of the case of Silvio Berlusconi. The main objective is to research, analyze and investigate what are the main factors of success of Berlusconi’s political communication within the framework of political marketing. The analysis is based on publications and bibliography found while examining the three chosen indicators, that were determined as key elements in political communication, following the models of political marketing. Lastly, the thesis draws a parallel between the communication styles of S. Berlusconi and Donald J. Trump.
Vedoucí práce: Květa Olšanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses